Legal framework of the Islamic banking in the United Kingdom and the Republic of Ireland - Hasan, Faheem (Riga Graduate School of Law, 2018)
The thesis explores the Islamic banking concept in the legal framework of the United Kingdom and the Republic of Ireland. The main objective is to focus on the legal and regulatory aspects of Islamic banking and finance in the United Kingdom, and the Republic of Ireland. As Islamic banking has entered the market with conventional banking in the United Kingdom and the Republic of Ireland, both countries have legal rules and regulation to control Islamic banking and financial transaction.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law